"Affiliate Marketer a Decent Work for Generation Z in Indonesia?" - Arlan Nugraha; Monica Aulia Pratiwi; Dwi Muharni Ardenis; Nurfatimah Amany; Sarah Sabir Ahmad; Anggraini Sukmawati (TIJAB (The International Journal of Applied Business))
Background: Affiliate marketers have grown significantly as they serve as promoters, connecting e-commerce platforms with social media audiences and providing profitable income opportunities.